Analysis Of The Application Of The Full Costing Method In Calculating The Cost Of Goods Produced (Cogs) Caftan For Determining Selling Prices: (Case Study On Caftan Production At Viahijab Store) - Candrika, Dwi; Alam, Iskandar Ali (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
This research was carried out to analyze the application of the full costing method in calculating the cost of produced (COGS) of caftans for determining selling prices. This research was carried out at the Viahijab Store using qualitative analysis techniques, where data has collected through interviews, observations, and literature studies. From the results of research that has carried out, the calculation of the cost of produced (COGS) and selling price using company calculations produces lower prices when compared to using the full costing method. Where the results of selling price calculations using the company method produce Rp. 186,540.3 per Caftan, while the calculation results from full costing are Rp. 200,040.3 per piece, this shows a difference of Rp. 13,500 per piece of Caftan. This is due to the difference in cost between the company method and the full costing method.